Enhancing literacy and optimizing anti-bullying character development through a service-learning approach at SDN 3 Ujungbatu - Andriyani, Santi; Hamidaturrohmah, Hamidaturrohmah; Azizah, Noor; Khasan, Mohammad; Meimaharani, Rizkyasari; Amalia, Miza Nur; Safitri, Anggun Rizkya (Universitas Muhammadiyah Magelang, 2025)
Mastery of literacy and character remains a challenge at the elementary school level, as observed at SDN 3 Ujungbatu Jepara. This community service (PkM) activity aimed to enhance teachers' competency in developing students' literacy skills and managing anti-bullying prevention programs. Utilizing a service-learning approach encompassing socialization, training, mentoring, and reflective evaluation, the program achieved significant improvements. Results showed an 89% increase in partners' insight regarding learning innovations and bullying prevention, and an 87.5% improvement in teachers' skills in leveraging technology for literacy and anti-bullying initiatives. Furthermore, digital journaling application proved effective in implementing anti-bullying attitudes and enhancing students' literacy skills through daily reflections, with an 88.5% success rate. The impact of this training and mentoring directly contributed positively to the increased competency and creativity of the partners.